THE OMNIPRESENCE OF GOD IN THE VIEWS OF STRONG AND PANNEBERG COMPARED TO A BIBLICAL ANALISYS - Costa, Marcio (Revista Hermenêutica (descontinuada), 2008)
RESUMO A discussão a respeito da onipresença de Deus iniciouseno primeiro século da era cristã com escritos dos Pais daIgreja e posteriormente foram expandidos durante Idade Média.Os desenvolvimentos do pensamento filosófico tambémocorreram simulteneamente, e por vezes entrelaçados aosconceitos da onipresença divina. Considerando o dominio dafilosofia nos tempos modernos, eu podero se de fato osensinamentos adquiridos da omnipresença de Deus não têmsido interpretados com a intençao de acomodar os desenvolvimentosfilosóficos. No presente material, um exame cuidadosofoi preparado a cerca das elaborações de Pannenberg eStrong com respeito a onipresença divina, e depois, umacomparaçao dos seus argumentos com as perspectivas adquiridasde um estudo biblico mais profundo sobre a onipresençade Deus. ABSTRACT The discussion about the omnipresence of God thatstarted with the Patristic writings at the first century AD wasexpanded through the Middle Ages and later in modern times.The development of philosophical thought also occurredsimultaneously and sometimes intertwined with the biblicalthought of divine omnipresence. Considering the philosophicaldominance of modern times, I have pondered if whether the biblical teachings of omnipresence are not being interpreted inorder to accommodate philosophical developments. In thismaterial, a careful examination is prepared about theelaborations of Pannenberg and Strong concerning theomnipresence of God and then, a comparison of theirarguments against the perspectives gained from a deep biblicalexamination of the omnipresence of God.